Effect of Volume Fraction and Alkalization Treatment on Mechanical Properties of Abaca Fiber Reinforced Composites as a Composite Board Substitute for Wood Products - Abubakar Dabet; Zulmiardi Zulmiardi; Ferry Safriwardi (Jurnal POLIMESIN, 2023)
Wood products are very popular products, especially in Indonesia. The drawback of wood products lies on their physical properties which are very susceptible to weathering in contact with water, causing wood products to be unsuitable for placing in parts of higher moisture. In addition, deforestation for processing wood products causes prolonged environmental damage. The main objective of this research is to make abaca fiber polyester composite material that can be used as a composite board for replacing wood product boards. The composite is made with varying the alkali solution treatment and fiber volume fraction by using the vacuum method (VARI).  Materials used in this study are abaca banana fiber, polyester resin, hardener and wax. The primary equipment used are such as tensile testing machine, freis machine, scanning electron machine (SEM), press machine, vacuum installation and digital scales as well as other supporting tools for composite preparation and fabrication. The research design for the preparation of composite test specimens used a polyester matrix and Abaca fiber reinforcement. Variation of alkalization solution used have rate of 1%, 3%, 5%, 7%, and 9%, and the volume fraction of abaca fiber is at 15%, 20%, 25%, 30% and 35%. The composite specimens test uses a tensile test ASTM D3039-76 standard, flexural test using the ASTM D790 standard and an impact test reaching the Charpy method. The results showed there are the highest tensile strength and modulus of elasticity were obtained from composites with specifications of 25%Vf and 5% alkali treatment of 186.89 MPa with a modulus of elasticity of 2.27 GPa. The highest bending strength value is found in the composite with a specification of 35%Vf and 5% alkali treatment with a bending strength value of 53,03 MPa. The highest impact strength value was found in the composite with a specification of 25%Vf and alkali treatment with a 5% concentration of 9,32 kJ/m2. Based on the mechanical properties data above, the composite specifications can be recommended for the manufacture of composite boards as a substitute for wood products at 35%Vf and 5% alkali treatment.